PENGARUH KEPUASAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. SEMEN TONASA - Florida Dessy Putri Sanuddin; A.M Rosa Widjojo (Modus, 2013)
This study aimed to clarify whether the variable Job Satisfaction and Work Motivation signifcantly infuence employee performance and to examine which variables are the dominant infuence of the two variables job satisfaction and work motivation on employee performance. This research was conducted in PT Semen Tonasa. The sampling technique using purposive sampling method a total of 220 employees. Data collection method used is to give a questionnaire to employees according to the research conducted. Data were analyzed using the Quantitative Methods using fve formulas Multiple Regression Analysis , correlation analysis , t-Tests , Test F and Test coefcient of determination ( R2 ) with the help of software SPSS 18.0 for windows. Results showed that together job satisfaction and work motivation signifcantly infuence employee performance. However , from the results of the t test , the variable job satisfaction has the most dominant efect when compared with work motivation. Correlation or relationship between Job Satisfaction and Motivation Work with Employee Performance PT. Cement Tonasa is equal to ( r = 0.365 ) and the coefcient of determination or R-square is a fgure of 0.133.KeywordsÂ  :Â  Job Satisfaction , Work Motivation and Employee Performance